Estetika Batik Tulis Motif “Bintang Laut” Pekalongan, Jawa Tengah (Kajian Estetika) - Fajrul Falah (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
Aesthetic research on Pekalongan batik is rare and limited. Several studies related to Pekalongan batik are studied from the economic aspect (production, distribution, and consumption) and health (disease). This study aims to reveal the aesthetics of motif batik "bintang laut" Pekalongan Central Java. The research approach used is aesthetics that include, unity, dominance and balance. This research is a literature study. The method used is descriptive analytics. The source of this research data is batik motif in Pekalongan. The selected and taken sample is one of the batik motifs in Pekalongan, "bintang laut". The results show batik motif "bintang laut" has a beauty and contains three esthetic elements. Miniature marine fauna and balanced color combinations and the size of different “bintang laut”, adding to the aesthetic impression and originality of batik that the way of making it still using the hand (manual).